Comprehensive transcriptomic analysis of cell lines as models of primary tumors across 22 tumor types - K. Yu (Nature Portfolio, 2019)
Cell lines are used ubiquitously in cancer research but how well they represent the tumor type they were derived from is variable. Here, the authors compare transcriptomic profiles of 22 tumor types and cell lines and propose a new comprehensive cell line panel for pan-cancer studies.